Adoption of ISO 9000 management standard in EU’s transition economies: the case of the Baltic states - Heras-Saizarbitoria, Iñaki; Arana, Germán; Cilleruelo, Ernesto (Journal of Business Economics and Management, 2013)
This article analyzes the dissemination of the main global management standards, the ISO 9000, within the transition economies of the European Union (EU). In the article, the specific case of the Baltic States is analyzed in depth. The work refers to the diffusion of the ISO 9000 standard in the Baltic States in terms of its certification intensity and sectorial distribution. Likewise, the work refers to the huge increase of certifications achieved by the countries and the other transition economies in the previous years of their adhesion to the European Union in years 2004 and 2007. The conclusions drawn in the article may be of interest both for academic and professional spheres of activity but, overall, for public-decisors.